2003
DOI: 10.2118/9781555630997
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Transient Testing

Abstract: Pressure Transient Testing presents the fundamentals of pressure-transient test analysis and design in clear, simple language and explains the theoretical bases of commercial well-test-analysis software. Test-analysis techniques are illustrated with complete and clearly written examples. Additional exercises for classroom or individual practice are provided. With its focus on physical processes and mathematical interpretation, this book appeals to all levels of engineers who want to understand how modern appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(28 citation statements)
references
References 0 publications
0
22
0
3
Order By: Relevance
“…Because of its flexibility in matching many different pressure responses, this model is often used even when there is no external information to justify its use. Geologically, the most direct rectangular reservoir model applies to wells in fault blocks which are limited by sealing faults [14,15]. The rectangular reservoir model also finds applications in fluvial channels, point bars, and offshore bar deposits where the end of the reservoir affects the test response.…”
Section: Rectangulermentioning
confidence: 99%
“…Because of its flexibility in matching many different pressure responses, this model is often used even when there is no external information to justify its use. Geologically, the most direct rectangular reservoir model applies to wells in fault blocks which are limited by sealing faults [14,15]. The rectangular reservoir model also finds applications in fluvial channels, point bars, and offshore bar deposits where the end of the reservoir affects the test response.…”
Section: Rectangulermentioning
confidence: 99%
“…O'Sullivan 6 demonstrated that the nonlinear PDEs that govern fluid flow in geothermal reservoirs can be collapsed to a set of ODEs by introducing the similarity variable η = r / Boltzmann's similarity variable. An equivalent and common choice in classical well-testing theory is the use of the transformationη = r 2 / t , which leads more neatly to the classical exponential integral solution in the case of single-phase equations. For the case of gas-condensate reservoirs, the introduction of the similarity variable η = r / in eq 3a yields or Following the same procedure, eq 6a can be rewritten as Equations 9 and 10 represent the system of ODEs that governs the flow of fluids in gas-condensate reservoirs, expressed in terms of the similarity variable. If one chooses pressure ( p ) and mass flux ( F ) as the dependent variables, this system of ODEs can be expressed as At this point, it is clear that the similarity method does collapse the original system of PDEs into a set of first-order ODEs in terms of a single independent variablethe similarity variable, η.…”
Section: Implementing the Similarity Variablementioning
confidence: 99%
“…For such conditions, the ODE system would be written as where the porous medium has been considered to be incompressible and k rg = 1 ( S g = 1) and k ro = 0 ( S o = 0). In order to obtain an analytical solution, the governing equations above are linearized by introducing the concept of pseudo-pressure, defined below: When the real gas law and the concepts of pseudo-pressure and gas isothermal compressibility ( c g ) are introduced, the above set of ODEs is recast in the following form: An analytical expression for the mass flux ( F ) can thus be obtained, by neglecting the remaining (usually weak) nonlinearity μ g c g its value being evaluated at initial conditionsand assuming that the porous medium is homogeneous: An alternative approach for the handling of the nonlinearity introduced by the term “μ g c g ” is to define an additional pseudo-variable (“pseudo-time”), which can be necessary at low-pressure operating conditions when compressibility variations with pressure can be significant. When eq 15a and the previous result are utilized, the classical exponential integral solution that governs the flow of a real gas through a porous medium is readily obtained: where E i is the exponential integral function.…”
Section: Noncondensing Gases:  Analytical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The diffusivity equation has been solved in dimensionless form [6]. "Chakrabarty with some other researchers provided a quantitative analysis of the effects of neglecting the quadratic gradient term on solving the diffusion equation governing the transient state [7].…”
Section: Introductionmentioning
confidence: 99%